Design, synthesis and biological activity studies of 1-aryl-3-(4-methoxybenzyl)ureas as proposed irreversible GSK-3 inhibitors in Alzheimer’s disease therapeutic development - Venter, Jana (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.